Efficiency of coated-urea materials in rice (Oryza sativa) - wheat (Triticum aestivum) system under partially reclaimed sodic soil - CHAUHAN, R P (The Indian Journal of Agricultural Sciences, 2013)
In a field experiment in partially reclaimed sadic soil different coated-urea materials, viz gypsum-coated urea, coal tar-coated urea, sulphur-coated urea at 3 levels of N, viz 40,80 and 120 kg/ha were compared with the prilled urea under rice (Oryza sativa L.) - wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system. Among coated-urea materials neem cake-coated urea and sulphur-coated urea were at par and significantly superior to the prilled urea with respect to the yield, yield attributes and N uptake and its recovery in rice-wheat system. However. maximum values of all these parameters were recorded with neem cake-coated urea. Grain yield of both the crops at 80 kg.N/ha as neem cake-coated urea and sulphur-coated urea were at par with those obtained with prilled urea at 120 kg N/ha. Average recovery of applied N with neem cake-coated urea was 32.1 and 37.5% in rice and wheat crops as against 20.5 and 27.1 % with prilled urea respectively. Neem cake-coated urea followed by sulphur-coated urea also maintained higher concentrations of NH 4’-N in soil under rice and NH 4’-N and N0 3’-N under wheat than prilled urea throughout the crop growth.